CONTROLLING PROBLEMATIC FINANCING: EFFORTS TO IMPROVE THE PROFITABILITY OF ISLAMIC BANKING THROUGH THE TWO STAGE LEAST SQUARE APPROACH - Ismul Fakhri Lubis; Dede Ruslan; Muhammad Fitri Rahmadana (CV. RADJA PUBLIKA, 2024)
The issue discussed is whether there is still a discrepancy or divergence between problematic financing (NPF) and profitability (ROA) from the general trend. On the other hand, Non-Performing Financing (NPF) and Return on Assets (ROA) interact in ways that significantly affect the financial performance of banks. This indicates the complexity of this relationship, suggesting a simultaneous relationship between NPF and ROA. The aim of this research is to understand the simultaneous relationship between profitability and problematic financing of Islamic banks in Indonesia. This study uses the Two Stage Least Square (TSLS) method, with financial ratio data from Islamic banks in Indonesia from 2010 to 2023, using quarterly data. Based on the simultaneous test results, there is a simultaneous relationship between the profitability model (ROA) and problematic financing (NPF). In the profitability equation model (ROA), BOPO affects the profitability of Islamic banks, while problematic financing and CAR do not have an effect. However, in the problematic financing equation model (NPF), profitability and CAR affect problematic financing in Islamic banks in Indonesia, whereas FDR does not affect operational cost reduction targets. Moreover, policies that emphasize increasing profitability through product diversification and capital enhancement (CAR) will help reduce the risk of problematic financing through issuing new shares or reinvesting profits, while product diversification can help increase revenue and reduce the risk of uncollectible financing.